A clinical and molecular analysis of Clostridium difficile strains isolated from Groote Schuur Hospital - Brock, Tunehafo Elisabeth (Department of Molecular and Cell Biology, 2016)
A clinical and molecular analysis of Clostridium difficile isolated from symptomatic patients at Groote Schuur Hospital was conducted in order to gain insight into the identity, epidemiology and pathogenesis of the various strains. C. difficile was detected and isolated by selective culture from stool specimens from 34 of the 162 symptomatic patients (20%). Three toxigenic-types were distinguished by PCR: A+B+ (47%), A-B+ (47%) and A-B- (6%), none of which harboured the binary toxin genes. Compared to the direct culture method, enzyme immunoassay-based detection tests (Meridian ImmunoCard and bioMérieux MiniVidas) were found to be lacking clinical sensitivity, while nucleic acid amplification tests (Hain Lifescience CDiff and Cepheid GeneXpert) were far more sensitive in the local clinical setting. PCR ribotyping identified all the A-B+ strains as PCR ribotype 017, which was the prevalent strain type (47%). Genotyping based on the tcdC gene and MLVA both grouped the ribotype 017 strains in a single clade. The antimicrobial susceptibility of all the isolates to metronidazole (MET), vancomycin (VAN), moxifloxacin (MOX) and erythromycin (ERY) were determined by the Etest method. All were sensitive to MET and VAN; however, four ribotype 017 strains displayed reduced susceptibility to MET. With regard to MOX, reduced susceptibly and full resistance were observed in 32% and 12% of the isolates, respectively, with all of these belonging to ribotype 017. MOX-resistant strains had a Thr82->Ile amino acid substitution in the GyrA enzyme and strains displaying reduced susceptibility to MOX had an Asp426->Asn amino acid substitution in GyrB. High-level resistance to ERY was observed in 47% of the isolates, which were primarily ribotype 017. ERY-resistant strains all harboured the ermB gene, suggesting that this was the genetic basis of the observed phenotype. Auto-aggregation analysis revealed that the ribotype 017 strains were significantly stronger auto-aggregators than the other ribotypes examined. Results of semi-quantitative RT-PCR analysis suggest that the expression level of the cwpV gene, encoding the CwpV protein, may play a role in auto-aggregation. In conclusion, this pilot study revealed that the GeneXpert method was the most accurate and sensitive technique for diagnosing CDI in the clinical setting at Groote Schuur Hospital. Ribotype 017 was the most prevalent strain type, and the antimicrobial resistance profile and increased auto-aggregation capacity of this ribotype may contribute to its high prevalence.